The Impact of Comedy on Racial and Ethnic Discourse. Issue 2 (21st March 2016) - Green, Aaryn L.; Linders, Annulla
Abstract : An overwhelming facet of race literature suggests that American society has entered an era of colorblindness; where instead of perpetuating racist ideology through blatant discriminatory legislation, racial differences are either understated or ignored entirely. These new racial processes are reflected in the policies of major social institutions, but also within popular culture. Yet, as made evident by the success of comedians such as Chris Rock and Dave Chappelle, stand‐up comedy challenges acceptable racial discourse, placing race in the forefront. Comedy persists as a facet of popular culture where racial difference is made apparent, yet ironically the art of comedy is usually overlooked by sociologists. What is lacking in the humor research is an understanding of how comedy creates an environment where race can be spoken about directly, and often times harshly. Through the analysis of focus groups, this study finds evidence to suggest that racial and ethnic comedy serves to both reinforce and wane racial and ethnic stereotypes, similarities, and differences. After watching stand‐up comedy clips of popular comedians, black and white respondents show both agreement and disagreement on the following: (1) the offensiveness of ethnic comedy, (2) stereotypes and perceived truths, and (3) the utility of ethnic comedy in everyday interactions. These findings are helpful in understanding how comedy serves as one of the few openly racialized facets of popular culture as well as uncovering some of the ways in which race works within the culture of a self‐proclaimed colorblind society.